Generating Java Code from UML Class and Sequence Diagrams - Parada, Abilio; Siegert, Eliane; de Brisolara, Lisane (Anais do Simpósio Brasileiro de Engenharia de Sistemas Computacionais (SBESC); 2011: Anais do I Simpósio Brasileiro de Engenharia de Sistemas Computacionais, 2011)
UML-based approaches provide abstraction to deal with the high complexity of embedded applications and when combined with Model-driven Engineering can also provide automation trough automatic code generation. This paper presents an approach to automatically generate structural and behavioral code from UML class and sequence diagrams.This approach is demonstrated through a case study and was validated by the implementation of a code generator.